(untitled) (Revista Archai, 2022)
By framing Aristotle’s dialectic in the broader context of scientific inquiry and demonstration, this paper is aimed at showing of what use the “reputable opinions” can be for grasping the principles of sciences, as declared in Topics I.2. It argues that such a use cannot imply ‒ at any stage of inquiry ‒ a replacement of the logic and intrinsic goals of demonstration by those proper to dialectic. However, it also defends a substantive (but still modest) contribution of dialectic ‒ beyond its well-attested methodological role in discarding contradictory opinions and its (possible though not germane to the context of Topics I.2) application to proving the principle of non-contradiction by means of refutation. This contribution consists in providing the preliminary accounts of facts in order to have scientific inquiry started, as required in Posterior Analytics II.8. To better appreciate how the proposed location of dialectic in a pre-demonstrative stage of inquiry is operational, the paper finally examines Physics IV.1-5.